An effective database management of the urban underground facilities and topographic information - Stankevičius, Žilvinas; Šlikas, Dominykas; Popovas, Darius (Geodesy and Cartography, 2015)
In developed countries the most accurate and reliable spatial data (M 1:500–1:1000) are extensively used. The same spatial object could be inscribed into separate systems: utilities companies have some systems, municipality collected catalogues of CAD data, separately developed real estate map. The same spatial objects are repeated and reiterated, unreasonable costs are incurred for their storage, the customers find it complicated to determine and select the best and appropriate spatial data required just for their own needs. This article suggests the solution of the problem. Authors have introduced the idea to compose and develop information system specialized for topography and infrastructure subsequently to be merged and coordinated. The model for data storage, data provision to the customers and service activities is defined. The available electronic services for the spatial data are described as advantageous for implementation on topographic maps, for inspection and monitoring of construction projects, for the issue of permits of excavation works and for the other activities.